Autoinhibition and activation mechanisms of the eukaryotic lipid flippase Drs2p-Cdc50p - Lin Bai; Amanda Kovach; Qinglong You; Hao-Chi Hsu; Gongpu Zhao; Huilin Li (Nature Communications, 2019)
The heterodimeric eukaryotic Drs2p-Cdc50p complex is a lipid flippase that maintains cell membrane asymmetry and its autoinhibition is released by PI4P binding. Here authors show cryo-EM structures of Drs2p-Cdc50p in apo and PI4P-activated form which reveal the structural changes upon PI4P binding.